Astaxanthin mitigates doxorubicin-induced cardiotoxicity via inhibiting ferroptosis and autophagy: a study based on bioinformatic analysis and in vivo/vitro experiments - Yin, Bowen; Ren, Jingyi; Liu, Xuanyi; Zhang, Yadong; Zuo, Jinshi; Wen, Rui; Pei, Huanting; Lu, Miaomiao; Zhu, Siqi; Zhang, Zhenao; Wang, Ziyi; Zhai, Yanyi; et al. (Frontiers in Pharmacology, 2025)
BackgroundDoxorubicin (DOX), a widely employed chemotherapeutic agent in cancer treatment, has seen restricted use in recent years owing to its associated cardiotoxicity. Current reports indicate that doxorubicin-induced cardiotoxicity (DIC) is a complex phenomenon involving various modes of cell death. Astaxanthin (ASX), a natural carotenoid pigment, has garnered significant attention for its numerous health benefits. Recent studies have shown that ASX has a broad and effective cardiovascular protective effect. Our study aims to investigate the protective effects of ASX against DIC and elucidate its underlying mechanisms. This has substantial practical significance for the clinical application of DOX.MethodsBioinformatic analyses were conducted using transcriptomic data from the gene expression omnibus (GEO) database to identify key mechanisms underlying DIC. Network pharmacology was employed to predict the potential pathways and targets through which ASX exerts its effects on DIC. In vitro experiments, following pretreatment with ASX, H9C2 cells were exposed to DOX. Cell viability, injury and the protein expression levels associated with ferroptosis and autophagy were assessed. In the animal experiments, rats underwent 4 weeks of gavage treatment with various doses of ASX, followed by intraperitoneal injections of DOX every 2 days during the final week. Histological, serum, and protein analyses were conducted to evaluate the effects of ASX on DIC.ResultsThe bioinformatics analysis revealed that ferroptosis and autophagy are closely associated with the development of DIC. ASX may exert an anti-DIC effect by modulating ferroptosis and autophagy. The experimental results show that ASX significantly mitigates DOX-induced myocardial tissue damage, inflammatory response, oxidative stress, and damage to H9C2 cells. Mechanistically, ASX markedly ameliorates levels of ferroptosis and autophagy both in vitro and in vivo. Specifically, ASX upregulates solute carrier family 7 member 11 (SLC7A11) and glutathione peroxidase 4 (GPX4), while downregulating the expression of transferrin receptor 1 (TFRC), ferritin heavy chain (FTH1) and ferritin light chain (FTL). Additionally, ASX enhances the expression of P62 and decreases levels of Beclin1 and microtubule-associated proteins light chain 3 (LC3).ConclusionOur results indicate that ferroptosis and autophagy are critical factors influencing the occurrence and progression of DOX-induced cardiotoxicity. ASX can alleviate DIC by inhibiting ferroptosis and autophagy.